Framework para transferência de conhecimento em instituição pública utilizando análise de redes sociais - Alves, Larissa Pereira Salles (2023)
To understand the dynamics and interactions that promote knowledge transfer, the use of technological tools has been a trend in public institutions. The technique of Social Network Analysis - SNA is one of these tools and, in this research, it was associated with the software Ucinet 6/NetDraw to obtain a diagnosis that can contribute to managers to make more strategic decisions regarding human capital. In this sense, and with the objective of evaluating the transfer of knowledge between employees, the informal social networks of friendship, trust, and information/knowledge were analyzed in the area of Human Resources of the Federal Institute of Espírito Santo - Ifes, which has 107 employees working in 21 campuses and the Rectory. As it has a qualified staff, the Ifes Staff Training Policy foresees actions to take advantage of the skills and competencies of the staff in training events within the institution itself. However, these actions have not been implemented yet. Thus, mapping the connections between employees, evaluating the flow of knowledge transfer, and identifying skills and competencies related to administrative activities can contribute to these actions. To this end, relational data were collected by means of an electronic questionnaire. With the results obtained it was possible to identify critical knowledge servers, their interaction patterns, and the roles they play in social networks, in order to collaborate to a more effective knowledge management and to minimize the loss of critical knowledge. Therefore, the technical product developed consists of a framework to help managers in the application of the technique and to identify servers capable of contributing to strategic actions for Training Policies.